2012
DOI: 10.1097/qad.0b013e328352d135
|View full text |Cite
|
Sign up to set email alerts
|

Safety of tenofovir use during pregnancy

Abstract: Objective To evaluate the association of tenofovir disoproxil fumarate (TDF) use during pregnancy with early growth parameters in HIV-exposed, uninfected (HEU) infants. Design US-based prospective cohort study of HEU children to examine potential adverse effects of prenatal TDF exposure. Methods We evaluated the association of maternal TDF use during pregnancy with small for gestational age (SGA); low birth weight (LBW, <2.5kg); weight-for-age z-scores (WAZ), length-forage z-scores (LAZ) and head circumfer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
74
1
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(82 citation statements)
references
References 26 publications
5
74
1
2
Order By: Relevance
“…Over time, substantial changes have occurred in prescribing patterns resulting in highly heterogeneous ART exposure, making it difficult to single out the effects of a single drug whilst also increasing the risk for confounding by indication. [3, 4] In particular, the use of TDF with a PI has generally been more common in the US than in African settings including ours,[16, 18, 19] and residual confounding may explain some of the differences observed in observational studies. Differences in co-occurring risk factors for poor child growth may however also contribute to the differential results.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Over time, substantial changes have occurred in prescribing patterns resulting in highly heterogeneous ART exposure, making it difficult to single out the effects of a single drug whilst also increasing the risk for confounding by indication. [3, 4] In particular, the use of TDF with a PI has generally been more common in the US than in African settings including ours,[16, 18, 19] and residual confounding may explain some of the differences observed in observational studies. Differences in co-occurring risk factors for poor child growth may however also contribute to the differential results.…”
Section: Discussionmentioning
confidence: 95%
“…In a large US cohort, the average length-for-age Z-score (LAZ) for 12-month old HEU infants exposed to TDF-containing ART regimens in utero was 0.14 lower than for those without TDF exposure. [3] In a similar but smaller cohort, TDF-exposed neonates had demonstrably lower bone mineral content (BMC) than their unexposed counterparts. [4] By contrast, preliminary data from the randomized IMPAACT-PROMISE trial conducted in Malawi, Zimbabwe, Uganda and South Africa showed no adverse association between TDF exposure and either birth length or neonatal BMC, although triple ART-exposed infants as a group had lower BMC than those exposed only to short course antiretrovirals for PMTCT.…”
Section: Introductionmentioning
confidence: 99%
“…In the APR, the prevalence of overall birth defects with exposure to TDF in the first trimester was 2.4% of 1612 live births and did not differ from the background rate in the USA [148]. Two studies showed no difference in fetal growth between infants exposed or not exposed to TDF [160,161]. TDF has limited penetration into breast milk, which limits its potential toxicity to the breastfeeding infant.…”
Section: Other Antiretroviralsmentioning
confidence: 98%
“…Additionally, children born to HIV infected women are already prone to undernutrition related to maternal factors yet nutrition plays a critical role in bone mass formation and mineralization during the fetal and infancy periods, 13,14 Some studies have indicated lower Bone Mineral Content (BMC) and lower height-for-age Z-score (HAZ) as well as lower head circumference-for-age Z-score (HCAZ) in infants exposed to TDF in-utero. [15][16][17] More recently, a study that was designed to evaluate the potential bone and kidney toxic effects of TDF among HIVinfected pregnant and breastfeeding women and their infants reported that there were significant decreases in BMC among newborns whose mothers received Protease Inhibitor-based ART during pregnancy compared to those who received only zidovudine (ZDV) during pregnancy. 18 Another first line antiretroviral, EFV is associated with vitamin D deficiency through multiple postulated mechanisms.…”
mentioning
confidence: 99%